Trichomycetes (Zygomycota) in the Digestive Tract of Arthropods in Amazonas, Brazil - Alencar, Yamile Benaion (Memórias do Instituto Oswaldo Cruz, 2020)
Eight species of Harpellales and three species of Eccrinales (Zygomycota: Trichomycetes) were found associated with the digestive tract of arthropods from terrestrial and aquatic environments in the central Amazon region of Brazil. New species of Harpellales include: Harpella amazonica, Smittium brasiliense, Genistellospora tropicalis in Simuliidae larvae and Stachylina paucispora in Chironomidae larvae. Axenic cultures of S. brasiliense were obtained. Probable new species of Enterobryus (Eccrinales), Harpella, and Stachylina (Harpellales) are described but not named. Also reported are the previously known species of Eccrinales, Passalomyces compressus and Leidyomyces attenuatus in adult Coleoptera (Passalidae), and Smittium culisetae and Smittium aciculare (Harpellales) in Culicidae and Simuliidae larvae, respectively. Comments on the distribution of some of these fungi and their hosts in the Neotropics are provided.